Après la mort, avant l’oubli - Fanny Bocquentin (Les Nouvelles de l’Archéologie, 2013)
The plastered skulls of the Near East have been the subject of frequent debates. This article re-examines their interpretation. It appears that a rather static vision of these objects of worship dominates the literature. The modification of the skulls concerns a very small portion of the adult population, for which it might be possible to refine the selection criteria if the remainder of the archaeological corpus (complete skeletons and acephalous skeletons) were integrated into the discussions. While of different craftsmanship, the faces modelled correspond to a stylistic canon which seems to ensure their effectiveness as mediators. The place of this practice in a complex chaîne opératoire for the treatment of the dead and their remains has been very little discussed. The secondary removal of skulls from the graves is a primary means of acquisition, but a series of preliminary anthropological observations suggests that several chaînes opératoires for treatment may have co-existed.